Antimicrobial resistance following mass azithromycin distribution for trachoma: a systematic review. Issue 1 (January 2019) - O'Brien, Kieran S; Emerson, Paul; Hooper, PJ; Reingold, Arthur L; Dennis, Elena G; Keenan, Jeremy D; Lietman, Thomas M; Oldenburg, Catherine E
Summary: Mass azithromycin distribution is a core component of trachoma control programmes and could reduce mortality in children younger than 5 years in some settings. In this systematic review we synthesise evidence on the emergence of antimicrobial resistance after mass azithromycin distribution. We searched electronic databases for publications up to June 14, 2018. We included studies of any type (excluding modelling studies, surveillance reports, and review articles) on community-wide distribution of oral azithromycin for the prevention and treatment of trachoma that assessed macrolide resistance, without restrictions to the type of organism. We extracted prevalence of resistance from published reports and requested unpublished data from authors of included studies. Of 213 identified studies, 19 met inclusion criteria (12 assessed Streptococcus pneumoniae ) and were used for qualitative synthesis. Macrolide resistance after azithromycin distribution was reported in three of the five organisms studied. The lack of resistance in Chlamydia trachomatis suggests that azithromycin might remain effective for trachoma programmes, but evidence is scarce. As mass azithromycin distribution for trachoma continues and is considered for other indications, ongoing monitoring of antimicrobial resistance will be required.